Institutional investors and real earnings management: A meta-analysis - Kabaciński, Bartosz; Mizerka, Jacek; Stróżyńska-Szajek, Agnieszka (Economics and Business Review, 2022)
The aim of the article is to examine the influence of institutional investor ownership on real earnings’ management (REM) practices through a meta-regression analysis (MRA) based on a sample of 225 estimations from 19 articles. Some of the available research suggests a mitigating role for institutional investors who can serve as external monitors and thus reduce earnings’ management activities which could have a negative impact on the company’s value. The results obtained from the basic model confirmed neither the hypothesis about the influence of institutional ownership on REM, nor the hypothesis about the existence of a significant publication bias. Using an augmented MRA model conclusions in different areas associated with structural and methodological heterogeneity were drawn. Differences in the impact of institutional ownership on real earnings’ management in different regions of the world, a dependence of the results on different data characteristics and differences in the results depending on whether the article was published in a top journal or not were found.